2022
DOI: 10.1002/cite.202100180
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Rhodium‐Catalyzed Hydroaminomethylation of 1‐Decene in a Thermomorphic Solvent System

Abstract: The homogenously rhodium-catalyzed tandem reaction of the hydroaminomethylation of 1-decene is investigated in a thermomorphic solvent system consisting of methanol and n-dodecane with the ligand sulfoxantphos. The influence of temperature, pressure and catalyst concentration is studied experimentally as the basis for kinetic modeling and parameter estimation. A kinetic model for the hydroaminomethylation is developed by connecting and reparametrizing a mechanistic approach for the hydroformylation with a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…It is important to highlight that independently of the catalyst and in the absence of morpholine, the substrate hydrogenation is favored. This behavior can be explained because, under HAM conditions (presence of amine), the concentration of the aldehyde intermediate is low due to the fast condensation with the amine, in agreement with our previous studies (monitoring of HAM reaction by GC); [14] in consequence, the hydroformylation reaction is shifted towards the aldehyde production and the formation of by‐products such as aldols can be minimized operating under HAM conditions, in accordance with the kinetic study recently reported by Hamel and coworkers [18a] . To sum up, the higher efficiency exhibited by the bimetallic system in comparison to the Rh monometallic catalyst towards the formation of the aldehyde 4 , can be associated to the cooperative effect of both metals more than that caused by the amount of phosphine available for rhodium, based on the effect of TPPTS in the HAM reaction (entries 3, 5 and 7, Table 2).…”
Section: Resultssupporting
confidence: 91%
“…It is important to highlight that independently of the catalyst and in the absence of morpholine, the substrate hydrogenation is favored. This behavior can be explained because, under HAM conditions (presence of amine), the concentration of the aldehyde intermediate is low due to the fast condensation with the amine, in agreement with our previous studies (monitoring of HAM reaction by GC); [14] in consequence, the hydroformylation reaction is shifted towards the aldehyde production and the formation of by‐products such as aldols can be minimized operating under HAM conditions, in accordance with the kinetic study recently reported by Hamel and coworkers [18a] . To sum up, the higher efficiency exhibited by the bimetallic system in comparison to the Rh monometallic catalyst towards the formation of the aldehyde 4 , can be associated to the cooperative effect of both metals more than that caused by the amount of phosphine available for rhodium, based on the effect of TPPTS in the HAM reaction (entries 3, 5 and 7, Table 2).…”
Section: Resultssupporting
confidence: 91%